Quality Assessment of the Clinical Practice Guideline for Tympanostomy Tubes in Children. (November 2018) - Sturm, Joshua J.; Huyett, Phillip; Shaffer, Amber; Kitsko, Dennis; Chi, David H.
Objectives: To determine the association between the introduction of statements 6 and 7 in the 2013 clinical practice guideline (CPG) for tympanostomy tubes in children and the identification of preoperative middle ear fluid (acute otitis media / otitis media with effusion [AOM/OME]) in children undergoing bilateral myringotomy and tube (BMT) placement. Study Design: Case series with chart review. Setting: Tertiary care children's medical center. Subjects and Methods: Patients who underwent BMT for recurrent AOM were retrospectively reviewed. We examined 240 patients before (BG; 2012) and 240 patients after (AG; 2014) the introduction of the CPG. Results: The baseline characteristics of the 2 groups were comparable. The total annual number of BMT placements performed at our institution decreased from 3957 (BG) to 3083 (AG). There was no significant increase in the rate of preoperative AOM/OME identification following CPG introduction (BG 78.3% vs AG 83.3%, P = .164). The rate of identification of AOM/OME in the operating room (OR) increased from 54.2% (BG) to 71.3% (AG, P < .001). The rate of identification of AOM/OME both in the clinic and in the OR increased from 55.1% (BG) to 71.3% (AG, P < .001). Cases with concordant clinic and OR AOM/OME occurred among younger children ( P = .045), those with fewer episodes of AOM ( P = .043), and those with shorter time between the clinic and OR dates ( P = .008). Conclusions: Following the introduction of the CPG, there was no change in the rate of identification of AOM/OME prior to recommending BMT placement in children with recurrent AOM. The lack of improved compliance with statements 6 and 7 may be related to multiple clinician- and patient-derived factors.